Bio-functionalized Gold Nanoparticles: A Potent Probe for Profound Antibacterial Efficiency through Drug Delivery System - Singh, Manoj; Manikandan, Subramanian; Yadav, Mukesh; Kumar, Sunil; Sehrawat, Nirmala; Meashi, Vikas; D, Diksha; Sharma, Pranjal; Sharma, Anil Kumar (Asian Journal of Biological and Life Sciences, 2020)
In the present manuscript, we reported extracellular biosynthesis of gold nanoparticles through extract of leaves from Dictyota dichotoma. Biosynthesized nanoparticles were characterized using UV– Vis spectroscopy, HRTEM, EDX and FTIR spectroscopy. The polyshaped gold nanoparticles of size 8±21 nm were synthesized. The antibacterial activities were observed by the agar well diffusion method for the action of Streptomycin and Gentamycin and their formulation with biocapped gold nanoparticles. The profound efficacies were supported by the increase in fold area of inhibition against the tested bacteria. The appropriate cause of this divergence has also been discussed due to suitable binding of biogenic gold nanoparticles with drugs and supports these findings to overcome the conflict of previously reported data.
Keywords: Antibacterial efficacy; Biomimetic; Dictyota dichotoma; Drug delivery systems